Flow estimation in nested basins through hydrologic regionalization: case study of the Agua Caliente and Retes Rivers - Watson-Hernández, Fernando (2026)
Estimating flow rates in regions with a scarcity of hydrometeorological data requires special techniques for this type of case, one of which is hydrological regionalization based on the transfer of parameters between river basins. The present study implemented the HBV Light hydrologic model to estimate flows in the Retes River sub-basin, located in the northern area of Cartago, Costa Rica, by transferring and applying parameters previously calibrated in the Agua Caliente River sub-basin. The statistical analysis of the results demonstrates the model’s satisfactory performance, as evidenced by a coefficient of determination (R²) of 0.865 and a Nash-Sutcliffe efficiency index (NSE) of 0.76 during the dry season (January-April). This substantiates the model’s aptitude in accurately replicating the hydrological dynamics within nested watersheds. Furthermore, it was ascertained that parameters such as soil water storage capacity (FC), maximum storage fraction (LP) and water distribution control (BETA) are congruent with those observed in previous studies conducted on analogous coverages. Despite the observed decline in accuracy during the rainy season, the study demonstrates that meticulous calibration and regionalisation based on physical and climatic characteristics facilitate the acquisition of reliable flow estimates. This methodological approach constitutes a contribution to the optimisation of water resource management in agricultural ecosystems, which are particularly vulnerable to climate variability and change. For the estimation of flow in regions with scarce hydrometeorological data, hydrologic regionalization based on parameter transfer between watersheds is a key methodology. The present study implemented the HBV Light hydrologic model to estimate flows in the Retes River sub-basin, located in the northern area of Cartago, Costa Rica, by transferring and applying parameters previously calibrated in the Agua Caliente River sub-basin.